Marketing mix (7P) analysis to increase room occupancy at Sthala, a tribute portfolio hotel, Ubud Bali - Shintya Dennis, Wayan Ayu (Review of Management, Accounting, and Business Studies, 2025)
Tight competition and the impact of the COVID-19 pandemic have significantly affected the hospitality industry, forcing hotels to adapt in order to survive and continue attracting tourists. One of the essential strategies to address this challenge is the implementation of an effective marketing approach. Among various marketing strategies, the marketing mix—particularly the 7P framework, which includes price, promotion, place, product, people, physical evidence, and process—is often used to enhance service offerings and increase occupancy rates. However, despite the application of these strategies at Sthala Ubud Bali, this study reveals that there remains a noticeable gap between the targeted and actual occupancy levels achieved. The aim of this research is to evaluate how the 7P marketing mix has been implemented at Sthala Ubud Bali to improve room occupancy. Data for this study were collected through documentation and in-depth interviews with the Revenue Manager. The results of the qualitative descriptive analysis indicate that challenges primarily lie in the areas of product, price, promotion, and place. It is recommended that the hotel prioritize improvements in these indicators to better meet customer expectations and ultimately increase occupancy performance.